Supervisi Gerakan Literasi Madrasah Berbasis Wall Magazine di MAN Insan Cendekia Aceh Timur - Nurbaiti, Nurbaiti; Yusrianti, Susi (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2024)
This research is entitled 'Supervision of Wall Magazine-Based Madrasah Literacy Movement at MAN Insan Cendeia East Aceh. This study aims to analyze the implementation and effectiveness of supervision of the madding-based madrasah literacy movement. The madrasa literacy movement is an initiative to increase reading interest and literacy skills of madrasah students. Making it a visual communication medium, it is used as a tool to convey information and develop students' literacy skills, but supervision is needed to ensure the proper and effective implementation of the school literacy movement. The research method used is qualitative research. Data collection techniques through observation, interviews, and documentation. The results of the analysis show that supervision plays an important role in ensuring the successful implementation of the school literacy movement. supervision consists of several components, including supervision of the manufacture and use of wall magazines, coaching and guidance for teachers and students, as well as evaluation of the effectiveness of the madrasah literacy movement as a whole. Through structured and directed supervision, errors and deficiencies in the implementation of the madrasah literacy movement can be identified and corrected, thereby ensuring that the goals of the literacy movement are properly achieved. The results of the study showed that all students were very enthusiastic in participating in magazine-based literacy activities. This research is expected to provide valuable insights and inspire further research in the field of madrasah literacy and curriculum development.